Effects of a Δ-9-fatty acid desaturase and a cyclopropane-fatty acid synthase from the novel psychrophile Pseudomonas sp. B14-6 on bacterial membrane properties. (1st December 2020) - Choi, Tae-Rim; Park, Ye-Lim; Song, Hun-Suk; Lee, Sun Mi; Park, Sol Lee; Lee, Hye Soo; Kim, Hyun-Joong; Bhatia, Shashi Kant; Gurav, Ranjit; Lee, Yoo Kyung; Sung, Changmin; Yang, Yung-Hun
Abstract: Psychrophilic bacteria, living at low and mild temperatures, can contribute significantly to our understanding of microbial responses to temperature, markedly occurring in the bacterial membrane. Here, a newly isolated strain, Pseudomonas sp. B14-6, was found to dynamically change its unsaturated fatty acid and cyclic fatty acid content depending on temperature which was revealed by phospholipid fatty acid (PLFA) analysis. Genome sequencing yielded the sequences of the genes Δ-9-fatty acid desaturase ( desA ) and cyclopropane-fatty acid-acyl-phospholipid synthase ( cfa ). Overexpression of desA in Escherichia coli led to an increase in the levels of unsaturated fatty acids, resulting in decreased membrane hydrophobicity and increased fluidity. Cfa proteins from different species were all found to promote bacterial growth, despite their sequence diversity. In conclusion, PLFA analysis and genome sequencing unraveled the temperature-related behavior of Pseudomonas sp. B14-6 and the functions of two membrane-related enzymes. Our results shed new light on temperature-dependent microbial behaviors and might allow to predict the consequences of global warming on microbial communities.